High‐Performance Flexible Gas Sensor Using Natural Rubber/MXene Composite for Selective and Stable VOC Detection - Na Kong; Ting Ren; Hui Yang; Mia Angela N. Judicpa; Ken Aldren S. Usman; Xu Zhao; Yanqiu Shao; Joselito M. Razal; Jinlong Tao; Jizhen Zhang (Advanced Materials Interfaces)
Abstract Flexible gas sensors are gaining interest for real‐time volatile gas monitoring. A natural rubber (NR)/MXene nanocomposite sensor is developed. Among the six selected target volatile gases, the composite sensor exhibited a strong response value (82% toward 100 ppm NH3) with the fastest response/recovery time (12.3 s/15.5 s) to NH3. The sensitivity showed a clear dependence of gases, suggesting a good selectivity to varying gases. Ti3C2Tx MXene gas sensors exhibited a very low limit of detection of 50–100 ppb for volatile organic compounds (VOCs) at room temperature. In addition, the NR/MXene sensor allows detection of the mixture of ammonia (NH3), dimethyl sulfoxide (DMSO), and acetone (C3H6O) and it shows good response depending on the total concentration of VOC gases. Furthermore, the flexible nanocomposite sensor exhibits stable sensing performance at different bending states (0‐120°) and shows 20‐day atmospheric stability. This sensor's ability extends to alcohol breath analysis, useful for drunk driving detection. This work paves the way to the possibility of using robust MXene‐based toward practical realization of electronic devices.